Phonetic Variation of Qaf and Jim in Egyptian and Saudi Arabic Dialects: Insights from Youtube Audiovisual Data and Popular Music - Ajidin, Salsa Hauna; Rismawati, Yanda; Ajidin, Asep; Ajidin, Farhan Alfaruq (Albariq: Jurnal Pendidikan Bahasa Arab, 2025)
Abstract This study analyzes the phonetic differences in the pronunciation of the letters Qaaf (ق) and Jiim (ج) in the Egyptian and Saudi Arabic dialects. Using a qualitative descriptive approach, the research draws data from audiovisual sources such as popular songs and YouTube videos featuring native speakers. The findings reveal that in Egyptian Arabic, Qaaf is frequently realized as a glottal stop (/ʔ/), and Jiim as a voiced velar stop (/g/). In contrast, in Saudi Arabic, both letters tend to retain their Classical Arabic pronunciation: /q/ for Qaaf and /d͡ʒ/ for Jiim. These phonetic differences are not merely articulatory; they also carry sociolinguistic significance, reflecting social identity, formality level, and cultural values. This research contributes to modern Arabic language learning by emphasizing the importance of understanding dialectal variation in pronunciation, especially in real-life communication across Arabic-speaking regions. Keywords: Qaaf, Jiim, Arabic dialects, phonetics, Egyptian Arabic, Saudi Arabic, sociolinguistics, language learning